2015
DOI: 10.1242/bio.201410645
|View full text |Cite
|
Sign up to set email alerts
|

mRNA expression analysis of the SUMO pathway genes in the adult mouse retina

Abstract: BSTRACTSumoylation is a reversible post-translational modification that regulates different cellular processes by conjugation/deconjugation of SUMO moieties to target proteins. Most work on the functional relevance of SUMO has focused on cell cycle, DNA repair and cancer in cultured cells, but data on the inter-dependence of separate components of the SUMO pathway in highly specialized tissues, such as the retina, is still scanty. Nonetheless, several retinal transcription factors (TFs) relevant for cone and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…SUMOylation is known to play an important role in retinal function [ 22 , 34 ] and in oxidative stress [ 21 ]. Interestingly, SUMO-1ylation was highly increased in retinas at time 24 (2.25 ± 0.16, P < 0.0001 vs t 0; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SUMOylation is known to play an important role in retinal function [ 22 , 34 ] and in oxidative stress [ 21 ]. Interestingly, SUMO-1ylation was highly increased in retinas at time 24 (2.25 ± 0.16, P < 0.0001 vs t 0; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that SUMO-1 plays an important role in the hyperactivation of JNK and Tau in a cellular model of oxidative stress and that curcumin, a strong antioxidant and anti-inflammatory natural molecule, was able to re-equilibrate the JNK–SUMO-1–Tau axis [ 21 ]. Since the involvement of SUMO in retinal function has been already shown [ 22 ], SUMO-1ylation levels in our ex vivo model has been investigated. In addition, photoreceptors and RGCs are known to be highly vulnerable to oxidative stress as that reactive oxidative species (ROS) imbalance is involved in many retinal diseases [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…How does the clock regulate zfYB-1 nuclear localization? One mechanism that has been implicated in clock-directed shuttling of proteins between the nucleus and cytoplasm is SUMOylation [ 5 , 35 ]. SUMOylation has been documented to time the nuclear entry of the BMAL1 clock protein.…”
Section: Resultsmentioning
confidence: 99%
“…A RT-qPCR was performed on mouse neuroretinas to assess the expression levels of the whole set of 87 mouse genes that encode the deubiquitinating enzymes belonging to the five aforementioned families (11 JAMM, 4 MJD, 15 OTU, 4 UCH, and 53 USP genes). Two reference genes, Rhodopsin and Cerkl , were included in the analysis due to their previously reported high and low levels of expression in the mouse retina, respectively [ 29 ]. The relative expression levels have been normalized to the expression of Gapdh , and the Z-score was calculated for the whole set of genes per each sample, so that they could be directly compared among them and between different samples.…”
Section: Resultsmentioning
confidence: 99%